KAJIAN YURIDIS PEGAWAI NEGERI SIPIL (PNS) TERKAIT DENGAN LARANG TERLIBAT DALAM PARTAI POITIK - SURYA, I KADEK ADI; SUARDANA, I WAYAN; PRATIWI, IDA AYU WINDHARI KUSUMA (GANEC SWARA, 2023)
A political party is an organization that is national in nature and was voluntarily formed by a group of Indonesian citizens on the basis of the same will and aspirations to fight for and defend the political interests of members, society, nation and state, and maintain the integrity of the Unitary State of the Republic of Indonesia based on Pancasila, based on the Law -Law Number 5 of 2014 concerning State Civil Apparatus, Civil Servants, hereinafter abbreviated as PNS, are Indonesian citizens who meet certain requirements, appointed as ASN Employees on a regular basis by staffing supervisor officials to occupy government positions. From the provisions of the norms that are regulated, civil servants are of course at the forefront in serving the community in relation to public services, and with these provisions, civil servants are restricted from participating as party members or administrators in accordance with the provisions of Article 3 of Government Regulation Number 37 of 2004 concerning Prohibition of Civil Servants Civilians Become Members of Political Parties. Before a civil servant becomes a member and/or administrator of a political party, the person concerned must first resign as a civil servant. That is, to ensure the neutrality of civil servants from the influence of political groups and parties, civil servants are absolutely prohibited from becoming members and/or administrators of political parties, so that this research can provide information to the wider community regarding the prohibition of civil servants from becoming members or administrators of political parties